Theodore Weld: Crusader for Freedom - Thomas, Benjamin P. (Rutgers Univisty Press New Brunswick, New Jersey, 1950)
"Measured by his influence, Theodore Weld was not only the greatest of the abolitionists; he was also one of the greatest figures of his time." Soon after his death in 1895 , the public forgot the man thus described by the Dictionary of American Biography, and even to historians he was little more than a name until a few years ago. It is as if Weld deliberately sought this obscurity; he refused to hold office in any of the antislavery organizations or to speak at their conventions; he avoided city life and worked in country districts; his writings were published anonymously, and he would seldom allow his speeches or his letters from the field to appear in print at all.
Keywords: Weld, Theodore Dwight -- 1803-1895; Abolicionistes